2007
DOI: 10.1111/j.1944-9720.2007.tb02871.x
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Language Students' Attitudes Toward Kanji and Their Perceptions on Kanji Learning Strategies

Abstract: This study aims at identifying interpretable factors underlying Japanese language learners' attitudes toward kanji and their self‐reported kanji learning strategies. It also examines the relationship between the two sets of belief factors. A questionnaire survey was conducted among Japanese language students at nine universities in the United States; 311 responses were subjected to exploratory factor analyses that identified six attitudinal factors and six strategy belief factors. Descriptive statistics indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 64 publications
0
20
0
2
Order By: Relevance
“…Cochran, McCallum, and Bell () similarly included students’ attributions for their own success and their attitudes toward learning a language, examining their relationship through the quantitative analysis of Structural Equation Modeling with the students’ achievement. Other studies have been more focused on perceptions of the learning situation specifically, linking perceptions of corrective feedback with their desire to participate (Yoshida, ), perceptions of certain instructional techniques with their choice of learning strategies (Mori & Shimizu, ), or perceptions of instructors with their motivation or anxiety (Ewald, ; Wesely, ). This emphasis on perceptions is notable, and it suggests that there is room for further research in this particular trait/learner orientation that might further explore the relationship between these perceptions, learner attitudes, and beliefs.…”
Section: The Trait or Learner Orientationmentioning
confidence: 99%
“…Cochran, McCallum, and Bell () similarly included students’ attributions for their own success and their attitudes toward learning a language, examining their relationship through the quantitative analysis of Structural Equation Modeling with the students’ achievement. Other studies have been more focused on perceptions of the learning situation specifically, linking perceptions of corrective feedback with their desire to participate (Yoshida, ), perceptions of certain instructional techniques with their choice of learning strategies (Mori & Shimizu, ), or perceptions of instructors with their motivation or anxiety (Ewald, ; Wesely, ). This emphasis on perceptions is notable, and it suggests that there is room for further research in this particular trait/learner orientation that might further explore the relationship between these perceptions, learner attitudes, and beliefs.…”
Section: The Trait or Learner Orientationmentioning
confidence: 99%
“…Current practice methods emphasize iterative practice over and over again, such as stroke strategy (Jiang and Zhao 2001), repeated learning (Haththotuwa Gamage 2003), rote learning (Shimizu and Green 2002) and rote memorization (Mori and Shimizu 2007), and they are still widely used in the CSL classroom. Shukong and miaohong are the two popular practice methods used for stroke order teaching.…”
Section: Practice Methodsmentioning
confidence: 99%
“…Drawing upon this conceptualization of kanji beliefs among teachers, Mori and Shimizu (2007) identified six factors underlying L2 Japanese students' perceptions about the nature of kanji , Kanji is fun ; Kanji is difficult ; Kanji has cultural value ; Kanji has future ; Kanji is useful ; Kanji learning requires special abilities , and six kanji learning strategies, morphological analysis , rote memorization , context‐based strategies , association methods , metacognitive strategies , and helplessness . Mori and Shimizu further demonstrated that L2 Japanese students considered rote memorization strategies most effective and metacognitive strategies least effective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Every foreign language has challenging features to learn. In case of Japanese, learning kanji (i.e., Chinese characters used in Japanese) is often viewed as a great challenge not only by students of Japanese as a second/foreign language (L2) (Gamage, 2003; Grainger, 2005; Mori & Shimizu, 2007; Mori, 2002) but also by Japanese language educators (Shimizu & Green, 2002). This is mainly because learning kanji involves the acquisition of the large volume of knowledge and skills including graphemic, semantic, and phonetic analysis of a number of multipart characters and multi‐character words (i.e., words that are composed of two or more Chinese characters).…”
Section: Introductionmentioning
confidence: 99%